Organisme Kriptik Crustacea pada Karang Mati (Dead Coral) Pocillopora di Perairan NCF Putri Menjangan, Buleleng, Bali Barat - Valessa Senshi Moira; Oktiyas Muzaky Luthfi (Journal of Tropical Marine Science, 2020)
Coral Reef is an ecosystem in symbiosis with groups of animals belonging to the Cnidaria phylum that can produce an outer skeleton of calcium carbonate. Coral reefs are known as highly complex and productive ecosystems with a high diversity of biota such as mollusks, crustaceans and reef fish. . Cryptic fauna are an important part of the food web in coral reef ecosystems. The cryptofauna organism is an important food source for certain coral carnivores, including fish, gastropods, mollusks and octopus. Dead coral can provide greater diversity of food resources than live coral. The method used is selected random (Purposive Random Sampling) with snorkeling depth of 5-7 meters, namely conducting a brief observation of the condition of coral reefs. Brachyura biota types found in dead corals in waters NCF Putri Menjangan, Buleleng, West Bali consists of 14 families from 3 stations namely: Eriphiidae, Trapeziidae, Macrophthalmidae, Squillidae, Porcellanidae, Parthenopidae, Xanthidae, Alpheidae, Enoplometopidae, Grapeziidae, Macrophthalmidae, Squillidae, Porcellanidae, Parthenopidae, Xanthidae, Alpheidae, Enoplometopidae, Grapeziidae, Macrophthalmidae, Squillidae, Porcellanidae, Parthenopidae, Xanthidae, Alpheidae, Enoplometopidae, Atelecyclida, Atelecyclida, Atelecyclida, Atelecyclida, Atelecyclida, Atelecyclida, Atelecyclida, Atelecyclidae, Grecidae Majidae and Pilumidae.